The interdependence of R&D, innovations, and productivity: case of Polish manufacturing companies - Zabłocka-Abi Yaghi, Adriana; Tomaszewski, Tomasz (Ekonomia i Prawo. Economics and Law, 2024)
Motivation: The structural model proposed by Crepon, Duguet, and Mairesse (the CDM model) in 1998 has been the workhorse of the empirical analysis of the relationship between firms’ innovation input and output and performance. Most research applying the CDM methodology shows a positive relationship between firms’ R&D, innovation, and productivity, primarily in highly developed countries. However, some studies do not confirm the universal nature of these relations, pointing to possible differences between countries, sectors, firm characteristics, sources of knowledge, types of innovation, or performance indicators. Aim: The study aims to explore the relationship between R&D expenditures, patent applications, and labour productivity among Polish manufacturing firms. The study applies a four-stage analysis of the innovation-performance relationship based on the CDM model. The method enables us to track the transformation of innovation input into output and its impact on the performance of companies. The analysis is based on the survey conducted in 2018 on a random sample of 1049 Polish manufacturing firms. Results: The results reveal interesting insights into the analysed relationship. Firstly, initial results confirm the vital role of cooperation, being an exporter, and functioning in specific markets for deciding to invest in R&D. Secondly, state aid, employees’ education, and being part of the capital group are crucial for the R&D intensity. The analysis confirms a statistically significant positive relationship between Polish manufacturing firms’ innovation input and output. However, the results of the last stage of the analysis indicate that the performance of manufacturing firms is unrelated to the innovation output.